Blue lightning - Cleeves, Ann (Cleeves, Ann. Shetland series., 2010)
Detective Inspector Jimmy Perez brings his fiancée home to Fair Isle, a birder's paradise, where strangers are viewed with suspicions and distrust. When a woman's body is discovered at the island's bird observatory, the investigation is hampered by a raging storm that renders the island totally isolated. Jimmy has to find clues the old-fashioned way, and he has to do it quickly. There's a killer on the island just waiting for the chance to strike again.